Manajemen Madrasah Berbasis Kemasjidan dan Implementasinya - Alwi, Muhamad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
Mosque-Based Madrasah Management is a process of managing an educational unit that organizes general and Islamic religious education that aims to form a generation of believers, knowledgeable, and good deeds by using available resources effectively and efficiently based on Islamic values in carrying out the functions and roles of the mosque. The method used in this study is qualitative research by applying a case study research design that is analyzed descriptively. The form of implementation of the Mosque-Based Madrasah (MBK) of the Istiqlal Jakarta Madrasah is as follows; a) Utilizing the main floor of the Istiqlal Mosque for prayer and teaching and learning activities, b) Utilizing the mosque corridor for teaching and learning activities and other activities such as hajj manasik, c) Using mosque facilities such as playgrounds, mosque fields, sports fields, mosque gardens for learning, d) Involvement of educators, education personnel, and students in activities organized by the Istiqlal Mosque, and e) Preparation of the Integrated Operational Curriculum (KOT) of the Istiqlal Jakarta Madrasah.